Arthroscopic Suprascapular Nerve Decompression: A Technique Video - Eric J. Cotter MD; Joshua H. Chang BS; Daanish Khazi-Syed BS; Catherine M. Hand BS; Camden J. Bohn BS; Chase Gornbein BS; Brian Forsythe MD (Video Journal of Sports Medicine)
Background: Suprascapular neuropathy is an uncommon but treatable cause of shoulder pain and dysfunction. The tortuous course of the suprascapular nerve puts it at risk for entrapment, particularly at the suprascapular and spinoglenoid notches. This video presents a reproducible method for suprascapular nerve decompression at the suprascapular notch. Indications: Massive rotator cuff tears, compressive masses, or ligament hypertrophy warrants prompt intervention to prevent subsequent denervation in the face of suprascapular neuropathy. In the absence of these pathologies, a trial of conservative management is advised. Patients who have unsuccessful conservative management and evidence of worsening weakness, atrophy, and denervation by electromyography are indicated for surgical intervention. Technique Description: Standard posterior, anterior, lateral, and anterolateral portals are established. The subdeltoid space is dissected following the coracoacromial (CA) ligament to the base of the coracoid to identify the transverse scapular ligament. In the presented case, the CA ligament has been debrided from a previous surgery, so an intra-articular approach was employed, opening the rotator interval to reach the base of the coracoid. A Neviaser portal is made for blunt dissection around the suprascapular notch, with care taken to protect the neurovasculature. A second medial Neviaser portal is used to pass a Kerrison to release the transverse scapular ligament. Nerve adhesions are then gently released with a probe. Results: A systematic review of 276 suprascapular nerve decompressions demonstrated good outcomes in terms of pain relief and function, and all athletes in the review returned to sport. A case series of 112 arthroscopic decompressions at the suprascapular notch found that patients achieved significant improvement in pain and strength, and none resulted in serious complications. These outcome studies support a level 4 video publication level of evidence. Discussion/Conclusion: The presented arthroscopic decompression technique treats suprascapular nerve entrapment at the suprascapular notch. Patients can expect to achieve a satisfactory outcome. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.